Learning Apple Compressor 4.1 - Schalk, Matt (Infinite Skills, 2014)
"In this Learning Apple Compressor 4.1 training course, expert author Matt Schalk teaches you how to effectively navigate through Compressor to design custom workflows for everyday encoding. This course is designed for the absolute beginner, meaning no experience with Compressor is required. You will start by learning the basic functions of Compressor, including batch properties, destinations, and locations. From there, Matt will teach you advanced settings and customization, such as image sequence settings and export components. This video tutorial will also cover how to work smarter in Compressor, including how to resize and retime, working with Final Cut Pro X and Motion 5, and distributed processing."--Resource description page.